Alat Pengukur Status Gizi Balita Berdasarkan Berat dan Panjang Badan Menggunakan Indeks Antropometri Dengan Metode Logika Fuzzy - Aditama Yudha Atmanegara; Ilham Ari Elbaith Zaeni; Dyah Lestari; Yandhika Surya Akbar Gumilang (JASIEK (Jurnal Aplikasi Sains, Informasi, Elektronika dan Komputer), 2022)
The health sector is crucial today. Various medical devices were created to facilitate the work of health workers. One of them is in the routine measurement of nutritional status by measuring the weight and length of children under five at the Posyandu. Several tools used to measure nutritional status are still working separately, and health workers are still calculating nutritional status manually. The purpose of this study is to design a tool that can measure the nutritional status of toddlers by using measurements of weight and length of toddlers simultaneously based on Anthropometric index calculations and comparing with fuzzy calculation analysis to support the results. The results of nutritional status, in this study, used 2 calculations, namely the calculation of the anthropometric index and the analysis of fuzzy measures. Based on the anthropometric index, the assessment of nutritional status used the variables of weight, body length, age, and gender (M/F). The calculation of these variables is processed in the Arduino Mega 2560 microcontroller and then displayed on the LCD and the Delphi program. A loadcell sensor is used to measure body weight, and a multiturn potentiometer is used to measure body length. Fuzzy calculation analysis used Mamdani, body length/age, and weight/body length methods as input from the anthropometric index and body weight/age to support calculations. The results of this study obtained a measuring tool for the nutritional status of toddlers that can bring up nutritional status based on anthropometric indexes and analysis of Fuzzy Mamdani calculations. This nutritional status measuring device can be used to make it easier for health workers to monitor the development of toddlers